Ski related differences in force production in uphill skiing with V2 skating technique - Ohtonen, O.; Lindinger, S.; Nieminen, V.-Matti.; Stöggl, T.; Linnamo, V. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
Force production during diagonal cross-country (XC) skiing has been often investigated (e.g. Komi 1985/1987, Vähäsöyrinki 2008, Lindinger 2009), but multidimensional force measurements during skating have rarely been performed. The role of gliding properties of skating skies for performance and biomechanical movement patterns is often discussed in XC ski racing but has not yet been investigated. The aim of the present study was to examine the effects of two differently prepared skating skis on performance, cycle characteristics and leg and pole force production during V2 skating at four different speeds.